1997
DOI: 10.1046/j.1365-2281.1997.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and circulatory haemodynamics before vasovagal syncope induced by orthostatic stress

Abstract: Vasovagal syncope is usually described as a sudden and transient loss of consciousness that resolves spontaneously. Cardiocirculatory changes are well described during and before syncope. However, changes in the cerebral oxygenation are not well defined. In this study, near-infrared spectroscopy (NIRS) was used to assess the cerebral oxygenation directly during 80 degree head-up (HU) tilt. To simulate central hypovolaemia, 500 ml of blood was drawn from each of 10 healthy subjects. Oxygenation index (OI) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 13 publications
(18 reference statements)
8
61
1
Order By: Relevance
“…Therefore, this study used [HHb] changes as a measure for cerebral oxygenation. [HHb], re¯ecting the change in match between oxygen consumption and delivery, 7,8 was signi®cantly increased in both groups during head-up tilt. Since cerebral oxygen demand is expected to be independent of body position, the increased [HHb] found indicates a decrease in oxygen delivery, ie cerebral blood¯ow, while meeting cerebral oxygen demand as indicated by the general absence of presyncope symptoms.…”
Section: Cerebral Oxygenation Changementioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, this study used [HHb] changes as a measure for cerebral oxygenation. [HHb], re¯ecting the change in match between oxygen consumption and delivery, 7,8 was signi®cantly increased in both groups during head-up tilt. Since cerebral oxygen demand is expected to be independent of body position, the increased [HHb] found indicates a decrease in oxygen delivery, ie cerebral blood¯ow, while meeting cerebral oxygen demand as indicated by the general absence of presyncope symptoms.…”
Section: Cerebral Oxygenation Changementioning
confidence: 91%
“…This non-invasive method has been described in greater detail in earlier studies. 7,8 Optodes were placed above the left eyebrow, using an interoptode distance of 4.5 cm. A pathlength factor of 6 was used.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study of fainters vs. nonfainters following withdrawal of 500 ml of blood plus head-up tilt (3), the fainters had decreased oxygen extraction in the cerebral tissues (positive oxygenation index, i.e., HbO 2 Ϫ dHb), while the nonfainters had increased oxygen extraction (negative oxygenation index), suggesting that increased tolerance may be due to increased cerebral oxygen extraction. The onset of presyncope is thought to be due to a mismatch between oxygen supply and demand in the brain (3,25), but this hypothesis has not been explored in relation to tolerance to maximal central hypovolemia.…”
mentioning
confidence: 99%
“…Cerebral oxygenation changes reflect cerebral functional activation (Colier et al, 1997;Colier et al, 1999;Kleinschmidt et al, 1996;Shibuya et al, 2004aShibuya et al, , 2004bShibuya and Tachi, 2006;Shibuya and Kuboyama, 2007;Shibuya et al, 2008;Obrig et al, 1996), and these changes can be measured using several techniques. Near-infrared spectroscopy (NIRS) and functional magnetic resonance imaging enable the noninvasive (Colier et al, 1999;Kleinschmidt et al, 1996;Mehagnoul-Schipper et al, 2000;Obrig et al, 1996, Obrig et al, 2000 In fact, Ide et al (1999) and Ide and Secher (2000) reported that prefrontal cortex activation (oxygenation) increased with increase in exercise intensity.…”
Section: Introductionmentioning
confidence: 99%